2006
DOI: 10.1128/jvi.02052-05
|View full text |Cite
|
Sign up to set email alerts
|

Autoactivation of the Epstein-Barr Virus Oncogenic Protein LMP1 during Type II Latency through Opposite Roles of the NF-κB and JNK Signaling Pathways

Abstract: Epstein-Barr virus (EBV)is associated with several human malignancies where it expresses limited subsets of latent proteins. Of the latent proteins, latent membrane protein 1 (LMP1) is a potent transforming protein that constitutively induces multiple cell signaling pathways and contributes to EBV-associated oncogenesis. Regulation of LMP1 expression has been extensively described during the type III latency of EBV. Nevertheless, in the majority of EBV-associated tumors, the virus is commonly found to display … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 70 publications
0
21
2
Order By: Relevance
“…For quantification of LMP1 mRNA in EBV-infected cells, Qp-EBNA1 was used as a control. Primers for LMP1 and Qp-EBNA1 have been described (34,35). …”
Section: Methodsmentioning
confidence: 99%
“…For quantification of LMP1 mRNA in EBV-infected cells, Qp-EBNA1 was used as a control. Primers for LMP1 and Qp-EBNA1 have been described (34,35). …”
Section: Methodsmentioning
confidence: 99%
“…This transactivation is dependent on cellular transcription factors and is mediated through several EBNA2-responsive elements at the LMP1 promoter. In the latency II pattern of gene expression, a few transcription factors, including STAT, IRF7, ATF4, ATF2, and NF-B (5,21,31,40,47), have been identified as candidates for LMP1 transactivation. It is becoming apparent that LMP1 transactivation in latency II may require the cooperation of several transcription factors, none of which seem to be absolutely critical in promoter activation.…”
Section: Discussionmentioning
confidence: 99%
“…While a number of EBNA2-independent LMP1 activators have been identified, none of them seem to be critical for LMP1 expression in latency II. Recent data suggest that LMP1 expression in latency II cells is mediated by cell signaling pathways that are activated by LMP1 itself (21,40).The complexity of LMP1 expression is further emphasized in a study by Lam et al (37). This study showed that LMP1 expression levels of individual cells in a clone of EBV lymphoblasts can range over 100-fold.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…On this point, nothing has been known regarding the potential function(s) of UL144 in regulating HCMV latency. However, its pleiotropic functions as an immune-modulating protein, several of which are reminiscent of the latent membrane protein 1 (LMP1) of Epstein-Barr virus (EBV) (40,43,44), suggest it as a potential candidate.…”
mentioning
confidence: 99%